Different Perspectives on Critical Factors in Heritage Language Development and Maintenance. (18th July 2019) - Flores, Cristina; Gürel, Ayşe; Putnam, Michael T.
Abstract: Heritage languages (HLs) are acquired in contexts of unbalanced input, or situations in which children receive primary exposure to the family/HL and experience an abrupt shift after the child begins formal schooling. As a consequence, HL speakers normally become more dominant in the environmental language, while the development of the HL is characterized by variable outputs. This means that HL speakers display more variation in their acquisition process and their "final state" competence compared to speakers of baseline varieties. This observation has raised thought‐provoking debates, which challenge long‐standing assumptions about language acquisition, development, and maintenance. This introduction provides an in‐depth description of the six contributions included in this volume and discusses how they challenge these assumptions. These contributions explore various attributes of HLs from diverse perspectives, using different research methods to advance our understanding of the various factors that facilitate, and in some instances, hinder the developmental trajectory of HLs. Abstract :